Kepatuhan Perawat dalam Pencegahan Penularan Infeksi Covid-19 - Dedeh Hamdiah; Ernawati Umar (Universitas Faletehan, 2021)
The high number of Covid-19 deaths among health workers is caused by compliance with the use of Personal Protective Equipment (PPE). Nurse compliance is the main key to success to prevent the transmission of Covid-19 infection. Risk factors for preventing the transmission of Covid-19 include the availability of PPE, peer support and need factor. This study aims to determine the relationship between risk factors and nurse compliance in prevention of the transmission of Covid-19 infection in Serang, Banten. The research used analytic observational with a cross sectional study design. The subjects of this study were all nurses who were actively working in Public Health Centers in Serang City. This study used total sampling and logistic regression statistical tests. The results showed that 48.3% of nurses did not comply with the use of PPE, and 55.2% of nurses stated that PPE was not available, 54% of nurses needed PPE to prevent the transmission of Covid-19 infection. There is a relationship between the availability of PPE (p=0.002), peer support (p=0.014) and need factor (p = 0.000) with the compliance of nurses to prevent transmission of Covid-19 infection. To conclude, there is a relationship between the availability of PPE and need factor with nurse compliance in prevention of the transmission of Covid-19 infection. Related parties, especially Public Health Centers and local Health Office, need to strive to fulfill the availability of adequate PPE as an aspect of the need for security and protection from the threat of transmission of Covid-19 infection.